The Transformation of Contemporary Media Studies: From Agenda Setting to Tool of Social Consensus - Bambang Mudjiyanto; Launa; Fit Yanuar; Nur Syamsi (Publikasi Inspirasi Indonesia, 2025)
The position of media studies continues to face academic debate: starting from a positive view (positivist media paradigm), a semi-critical perspective (postpositivist and constructivist media paradigms), a critical perspective (critical media paradigm), to a postmodernist/poststructuralist perspective. This qualitative study does not discuss the postmodernist/poststructuralist paradigm, but only looks at the position and function of media from a positivist, constructivist, and critical perspective. This study is qualitative with a descriptive-interpretive analysis approach. The results of the study show that constructivism and critical paradigms have different perspectives, sharpness, and levels of analysis in viewing the position and function of media from a social, cultural, and ideological perspective compared to the positivist paradigm